Failure of First Attempt Needle Decompression in Tension Pneumothorax: Case Report - Christianto Wisman; Boby Yaputra (Archives of The Medicine and Case Reports, 2022)
Tension pneumothorax can occur as a potentially life-threatening complication of chest trauma. Tension pneumothorax is commonly treated with needle decompression, both the 2nd intercostal space in the midclavicular line and the 4th/5th intercostal space in the anterior axillary. A 45 years old man came to our emergency department after blunt injury of the chest presenting tension pneumothorax with unstable hemodynamic treated with needle decompression using 14th (5 cm) gauge cannula at 2nd intercostal space midclavicular line, the patient felt comfortable and became hemodynamic stable, but chest radiograph evaluation showed no improvement tension pneumothorax. Several studies show the failure of needle decompression may be due to several factors such as chest wall thickness, cannula length, occlusion of the catheter, and location of the needle decompression. In this case, failure of needle decompression may be because of the occlusion due to catheter kinking so that the air cannot escape through the cannula and may also be caused by the insufficient length of the cannula to pass through the full thickness of the patient's chest wall.